SOME PROBLEMS OF MODERN STATE ROAD SAFETY AND THEIR SOLUTIONS - and (Municipal economy of cities. Series: «Economy science», 2017)
In article the analysis of dynamics and causes of the current state of traffic accidents in Ukraine compared with countries. Present dynamics of accidents in the Kharkiv region also specify which types of accidents prevail in the selected region. It was found that most of the accidents occur when not observing drivers and passengers traffic regulations for different reasons. These main factors that contribute to high levels of accidents and the basic principles concerning the measures implemented in Europe and the proposed fundamental changes are needed in the field of traffic safety in Ukraine. Implementation of the proposed measures would reduce the number of accidents on the roads of Ukraine, and reduce the severity of their consequences. Keywords: road safety, the level of road traffic accidents.